NAVIGATING HISTORICAL CYCLES: IBN KHALDUN’S ASHABIYYAH AND ALI SHARIATI’S SOCIETAL EVOLUTION - Rahmawati; Anisah Alamshah; Syamzan Syukur (Program Studi Sejarah Peradaban Islam, 2025)
Ibn Khaldun and Ali Shariati, pivotal figures in Islamic intellectual thought, have contributed meaningfully to how historians and sociologists understand the ways societies change over time and how historical cycles unfold. This paper seeks to integrate their significant insights in history and sociology, aiming to offer a cohesive framework of their ideas. By examining Ibn Khaldun’s concept of Ashabiyyah, which describes the cyclical rise and decline of civilizations, alongside Ali Shariati’s approach to societal evolution from an Islamic perspective, this synthesis highlights each thinker’s unique approach to social change. Drawing on their foundational works, the analysis explores Khaldun’s cyclical view of civilizations through Ashabiyyah and Shariati’s complex understanding of societal transformation. The authors aim to provide a comprehensive discussion, illuminating the interconnectedness of history and sociology through the perspectives of these two influential scholars.